THE IMPORTANCE OF THE COLLECTORIZATION POLICY IN THE RESTORATION OF UZBEKISTAN'S SKIN GROWING (World Conference on Social Sciences, Law and Public Policy, 2026)
This article analyzes the role of collectivization policy in the restoration of sericulture in Uzbekistan. The study examines the impact of collectivization processes on the development of the industry, changes in the organization of production, and the formation of new management systems in agriculture. Particular attention is paid to the increase in cocoon production, the expansion of the raw material base, the efficiency of labor resource utilization, and state support measures. The article also evaluates the positive and negative aspects of collectivization policy and its role in the development of the sericulture industry.
Keywords: sericulture, collectivization, agriculture, Uzbekistan, Soviet period, production, economy, raw materials, labor resources, state policy.